The Relationship between Dietary Habits and Gastroesophageal Reflux Disease: A Two-sample Mendelian Randomization Study - Ou, Haiya; Huang, Hongshu; Ye, Xiaopeng; Lin, Haixiong; Wang, Xiaotong (Current Medicinal Chemistry, 2025)
PurposeThis study aimed to explore the potential causal relationship between dietary habits and Gastroesophageal Reflux Disease (GERD).MethodsUsing the inverse-variance weighted method, a two-sample Mendelian randomization (MR) analysis was performed to investigate the causal relationship between 22 dietary habits and GERD. The stability and reliability of the results were assessed using leave-one-out analysis, heterogeneity tests, and tests for horizontal pleiotropy based on the effect measure odds ratio (OR) and 95% confidence interval (CI).ResultsThe results of the MR analysis indicated a positive association between alcohol drinking (OR=1.472; 95% CI, 1.331 to 1.629; p<1.0×10-3) and salt added to food (OR=1.270; 95% CI, 1.117 to 1.443; p<1.0×10-3) with the risk of GERD. Conversely, bread intake (OR=0.613; 95% CI, 0.477 to 0.790; p<1.0×10-3), cereal intake (OR=0.613; 95% CI, 0.391 to 0.677; p<1.0×10-3), cheese intake (OR=0.709; 95% CI, 0.593 to 0.846; p<1.0×10-3), dried fruit intake (OR=0.535; 95% CI, 0.404 to 0.709; p<1.0×10-3), fresh fruit intake (OR=0.415; 95% CI, 0.278 to 0.619; p<1.0×10-3), and oily fish intake (OR=0.746; 95% CI, 0.633 to 0.879; p<1.0×10-3) were negatively associated with the risk of GERD. Sensitivity analysis showed no evidence of reverse causation, pleiotropy, or heterogeneity.ConclusionAlcohol and salt added to food raised GERD risk, while bread intake, cereal intake, cheese intake, intake of certain dried fruits and certain fresh fruits, and oily fish lowered it. Our study affirms the potential causal link between these diets and GERD, offering insights into targeted prevention strategies.
Keywords: renal disease